Transition between peritoneal dialysis and home hemodialysis in Belgium and France in the RDPLF - Christian Verger; Emmanuel Fabre (RDPLF, 2020)
A renewed interest in home hemodialysis has emerged in recent years, favored by the availability of new dialysis machines and encouraging publication about  daily hemodialysis. Since 2013, the RDPLF has become a home dialysis registry that records the data of patients treated with peritoneal dialysis and those treated with home hemodialysis, all techniques combined. Nine Belgian centers and fifty seven French centers communicate information about their patients treated by hemodialysis at home. In the RDPLF centers, 56% of Belgian home hemodialysis patients are treated with daily hemodialysis, in France 83% of home patients are on daily dialysis. This French difference however is not representative of the whole country but can be explained through recruitment of new centers already involved in peritoneal dialysis and convinced by the interest of continuaous daily treatment. In both countries, 13% of home hemodialysis patients have been previously treated with peritoneal dialysis with an interim period of in-center hemodialysis or transplantation. The median duration of in center hemodialysis is 10 months with extremes ranging from 2 months to 25 years. PD patients treated secondarily in home hemodialysis are mainly young, non-diabetic and independent patients. Early information in patients who have a risk of peritoneal dialysis failure, and the provision of materials allowing both techniques would reduce or abolish a transient transfer to in center hemodialysis  and would ensure home care in patients who prefer.